2012
DOI: 10.4028/www.scientific.net/amr.550-553.1691
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Granular Activated Carbon Adsorption Method for Separation of Levulinic Acid from Formic Acid

Abstract: Levulinic acid (LA) is a new versatile platform chemical derived from renewable non-food biomass. A major challenge in the purification of LA from biomass hydrolysate is the separation of LA and formic acid. A novel granular activated carbon (GAC) adsorption and separation of LA and formic acid were investigated in this work. Adsorption equilibria elucidated that LA preferentially adsorbed onto GAC than formic acid. Mixed solution of LA and formic acid was fed into the GAC packed-bed at 30°C, then formic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Some methods of separation and purification of LA from preview literature could be applied in our experiments. A granular activated carbon (GAC) adsorption method for separation of lanthanum and formic acid was studied ( Liu et al, 2012 ). Kim et al also confirmed that LA could be effectively separated from 5-HMF by ED ( Kim et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some methods of separation and purification of LA from preview literature could be applied in our experiments. A granular activated carbon (GAC) adsorption method for separation of lanthanum and formic acid was studied ( Liu et al, 2012 ). Kim et al also confirmed that LA could be effectively separated from 5-HMF by ED ( Kim et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…No 5-HMF and furfural was observed in the eluent, and the separation of LA and these two substances were achieved. The eluate contained a low concentration of formic acid, which can be further separated by activated C. Liu et al [36][37][38][39] used D301 anion exchange resin to remove substances such as sugars and 5-HMF, then decolorized the eluate by AB-8 macroporous resin, and finally separated LA and formic acid by a novel granular activated C column. In summary, the G10PTEPA resin realized a high decolorization rate and initially separated LA from hydrolysate, which simplified the purification process of LA.…”
Section: Elutionmentioning
confidence: 99%
“…8 Although several recovery methods of 4-oxopentanoic acid from aqueous media are available, the separation of this acid by adsorption is limited, which is evident from the literature. A novel granular activated carbon was used to recover LA from formic acid elution by Liu et al 9 Adsorption equilibrium revealed that levulinic acid got satisfactorily adsorbed on the surface of activated carbon than formic acid. LA separation was achieved with high yield and better purity.…”
Section: Introductionmentioning
confidence: 99%